2019
DOI: 10.1002/jsfa.9808
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of volatile compounds and sensory characteristics of edible green seaweed (Ulva rigida) during storage at different temperatures

Abstract: BACKGROUND: Edible seaweeds are one of the most important resources that currently exist for their multiple uses and applications. Like other food types, during their storage there are significant changes in sensory characteristics associated with loss of freshness and with production and/or degradation of their volatile compounds. In this study, multiple headspace sorptive extraction (MHSSE) coupled with gas chromatography/mass spectrometry (GC/MS) detection has been applied to an edible green seaweed (Ulva r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…For the oven-dried S. ramosissima , the main volatile compounds detected were hexanal (34.16%), 3-hexen-1-ol (1.80%), 2-methylbutanoic acid (7.84%), heptanal (5.14%), 1-octen-3-ol (3.0%), 6-methyl-5-hepten-2-one (3.92%), p -cymene (3.08%), limonene (10.18%), 3,4-dimethylcyclohexanol (7.31%), β-cyclocitral (1.97%), and 3,5-octadien-2-one (1.19%). In general, linear and branched chain aldehydes contribute with herbaceous and grassy-green aromas [ 54 ], namely hexanal, which is responsible for herbal and grassy-green odors [ 52 , 53 ]. Compounds such as 2-methylbutanoic acid, heptanal, 1-octen-3-ol, and 3,5-octadien-2-one are described as responsible for some off-odors including sour, penetrating oil-like, mushroom-like, and marine odors, respectively, but their contribution to the aroma depends on their limit of detection [ 50 , 53 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the oven-dried S. ramosissima , the main volatile compounds detected were hexanal (34.16%), 3-hexen-1-ol (1.80%), 2-methylbutanoic acid (7.84%), heptanal (5.14%), 1-octen-3-ol (3.0%), 6-methyl-5-hepten-2-one (3.92%), p -cymene (3.08%), limonene (10.18%), 3,4-dimethylcyclohexanol (7.31%), β-cyclocitral (1.97%), and 3,5-octadien-2-one (1.19%). In general, linear and branched chain aldehydes contribute with herbaceous and grassy-green aromas [ 54 ], namely hexanal, which is responsible for herbal and grassy-green odors [ 52 , 53 ]. Compounds such as 2-methylbutanoic acid, heptanal, 1-octen-3-ol, and 3,5-octadien-2-one are described as responsible for some off-odors including sour, penetrating oil-like, mushroom-like, and marine odors, respectively, but their contribution to the aroma depends on their limit of detection [ 50 , 53 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Peaks above 1200 cm −1 in both seaweeds represent the phenol groups that indicate that both seaweeds are flourish in antioxidants, which can be utilized in development of functional food and their extract may be characterized for the bioactive compounds which can be useful in nutraceuticals formulation. It has also been reported that marine macroalgae produces wide variety of volatile organic compounds such as hydrocarbons, terpenes, phenols, alcohols, aldehydes, ketones, esters, fatty acids, and halogen or sulfur-containing compounds, which are responsible for its characteristic flavor and freshness, and these volatile compounds have been well identified by Spanish researchers in U. rigida [34].…”
mentioning
confidence: 94%
“…The respondent from the food sector emphasizes the need to create positive taste experiences from seaweed and take advantage of current trends on local, sustainable, healthy and vegetarian/vegan foods. In this context, efforts must be made to identify the effects of relevant processing and storage methods on the sensory properties of the products (Stévant et al 2018(Stévant et al , 2020Sánchez-García et al 2019) and to develop tasty ingredients from seaweeds. A LFCS may act as a platform for collaboration between seaweed producers, processors and industrial users of cultivated biomass to establish quality standards for food products and develop adapted processing strategies.…”
Section: Cultivated Seaweeds For Food and Feed Applicationsmentioning
confidence: 99%